1997
DOI: 10.1128/mcb.17.11.6618
|View full text |Cite
|
Sign up to set email alerts
|

Stat1 Serine Phosphorylation Occurs Independently of Tyrosine Phosphorylation and Requires an Activated Jak2 Kinase

Abstract: Gamma interferon (IFN-␥) induces both tyrosine and serine phosphorylation of Stat1. Stat1 serine phosphorylation is required for maximal transcriptional activity of Stat1. In this report, we present evidence that Stat1 tyrosine phosphorylation is not a prerequisite for Stat1 serine phosphorylation, although an active Jak2 kinase is required for both phosphorylation events. Stat1 serine phosphorylation occurs with a more delayed time course than tyrosine phosphorylation. The occurrence of serine phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
110
2
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 25 publications
18
110
2
1
Order By: Relevance
“…Previous work on the interactions between MAPK and Jak-Stat pathways has focused on MAPK-dependent phosphorylation of a conserved carboxyl-terminal serine residue in the Stat proteins themselves (46, 58 -61, 66, 71-79). There is general agreement that phosphorylation of Stat1 and Stat3 on serine 727 enhances the transcriptional potency of tyrosinephosphorylated Stat dimers (46,61,74,76,78,79), and one study suggests that DNA binding is enhanced as well (72). However, several studies have suggested that serine phosphorylation of Stats actually suppresses tyrosine phosphorylation and DNA binding (58,60,66,80), although only one of these studies tested this directly using a mutated Stat (58).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on the interactions between MAPK and Jak-Stat pathways has focused on MAPK-dependent phosphorylation of a conserved carboxyl-terminal serine residue in the Stat proteins themselves (46, 58 -61, 66, 71-79). There is general agreement that phosphorylation of Stat1 and Stat3 on serine 727 enhances the transcriptional potency of tyrosinephosphorylated Stat dimers (46,61,74,76,78,79), and one study suggests that DNA binding is enhanced as well (72). However, several studies have suggested that serine phosphorylation of Stats actually suppresses tyrosine phosphorylation and DNA binding (58,60,66,80), although only one of these studies tested this directly using a mutated Stat (58).…”
Section: Figurementioning
confidence: 99%
“…2) Inhibition of Stat3 mutated at serine 727 (Fig. 9); it is unlikely that inhibition of Stat3-S727A can be explained on the basis of phosphorylation of other serine residues in Stat3, since phosphopeptide mapping experiments have shown that serine 727 is the predominant site of serine phosphorylation (46,58,72,74). 3) Inhibition of IL-6 activation of ERKs (which are downstream of Jaks, but independent of Stats) occurred in primary fibroblasts, where, in contrast to hemopoietic cells, IL-6 activation of ERKs was detectable (L. Ivashkiv, unpublished observations).…”
Section: Figurementioning
confidence: 99%
“…When stimulated by EGF, STAT3 is tyrosine-phosphorylated at residue 705 and translocates to the nucleus, either as a homodimer or as a heterodimer with the 91 kDa STAT1α, where it binds to selected EGF-responsive DNA sequences [5]. STAT3 and STAT1α both contain a C-terminal serine residue (residue 727) that is subject to phosphorylation by the mitogen-activated protein kinase (MAPK) pathway [6,7], as well as by other serine kinases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A different study showed that the DNA-binding domain of STAT2 is functional, as two amino acid substitutions (V453I, V454I) affected IFN-␣-mediated biological responses that were STAT2 dependent, but ISGF3 independent (Brierley and Fish, 2005). A conserved serine residue found in the TAD of STAT1, STAT3, STAT4, and STAT5 must be phosphorylated to maximally drive gene expression Zhu et al, 1997;Morinobu et al, 2002;Xue et al, 2002;Pilz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of STAT1 or STAT2 in the conserved arginine in the SH2 domain or mutation in the conserved tyrosine phosphorylation site abrogates dimerization or nuclear translocation (Gupta et al, 1996;Li et al, 1997;Mowen and David, 1998). Although a mutation in the conserved serine 727 found in the transactivation domain (TAD) of STAT1, as well as in STAT3 and STAT4, impairs transcriptional activity Zhu et al, 1997;Morinobu et al, 2002), a mutation in the N-terminal domain of STAT1 (F77A) impairs its oligomerization, tyrosine dephosphorylation, and gene transcription (Meyer et al, 2004). In contrast, forced dimerization of STAT1 by mutation of two conserved cysteine residues within the SH2 domain renders cells more responsive to the apoptotic effects of IFNs (Sironi and Ouchi, 2004).…”
Section: Introductionmentioning
confidence: 99%